Pengembangan Perangkat Pembelajaran Matematika dengan Pendekatan Realistic Mathematics Education (RME) pada Materi Prisma Dan Limas Kelas VIII SMP - Melinda, Nur Oktavia; Ariawan, Rezi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
This study aims to produce mathematics learning tools in the form of Lesson Plans (RPP) and Student Worksheets (LKPD) with Realistic Mathematics Education (RME) Approaches in Junior High Schools that have been tested valid. This study uses the development or R&D method using the ADDIE model, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The data collection technique used is validation data from experts. The data analysis technique is validation data analysis. From the study results, the results of the RPP validation were 86.77% in the very valid category, and the LKPD validation results were 85.41% in the very valid category. This study obtained that the mathematics learning tools with the Realistic Mathematics Education (RME) Approach in Junior High Schools were very valid.